ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI BEKERJA & BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PT ABC - Bangsa , Bintang Kusuma; Adriansyah , Ahmad (Ibs Press, 2025)
This study aims to determine the effect of transformational leadership, work motivation andorganizational culture on the performance of PT ABC employees. In order to minimize thespread of the COVID-19 virus in the work environment and comply with applicable healthprotocols, primary data collection was obtained using an online questionnaire via Google Form which was distributed in December 2020. This study used SEM data analysis techniques with the type of Partial Least Squares (PLS-SEM) and the number of respondents who participated was 42 respondents who were employees of PT ABC. Based on the results of the study, it was found that work motivation had a significant effect on the performance of PT ABC employees with a P-Value = 0.000 <0.05, while work motivation and organizational culture had no effect on the performance of PT ABC employees with a P-Value of 0.470 and respectively. 0.275, where both values are> 0.05.